(untitled) (Journal of School Administration Research and Development, 2023)
Teachers are prematurely leaving the profession at substantially high rates. The purpose of this research was to (a) collect and analyze factors linked to retention and potential attrition (i.e., how often a teacher considers leaving the profession), (b) provide specific and updated data on the causes of this problem along with potential solutions, and (c) meet the objective of improving retention policy and practice at all the levels of leadership within the education system. The sources used for this study are extensive literature and a mixed-methods survey about experiences sent by email to teachers across the state of California. The survey collected usable responses from 2,196 teachers about their experiences with teacher preparation programs, induction or mentorship programs, and their first five years of teaching. The researcher analyzed the responses to determine the relationships between the experiences and to make recommendations for leadership. The findings of this research show that teachers across the State of California feel high amounts of stress in their first five years of teaching, in addition to being generally unprepared for the profession and feeling unsupported in their induction programs. All of these factors are related to the frequency with which teachers consider leaving the profession throughout their careers. Recommendations for leadership include creating hands-on, practical, specific experiences prior to and in the early years of teaching; building better relationships between all staff members, including mentors; reducing the workload for teachers generally; and developing clearer communication and transparency between all stakeholders throughout the educational system.